SOLUTION —
Let, $ \quad p(x)=x^3-6 x^2+3 x+10$
and $(a),(a+b)$ and $(a+2 b)$ are the zero of $p(x)$.
We know:
Sum of the zeroes $=-\left(\right.$ coefficient of $\left.x^2\right) \div$ coefficient of $x^3$
$\Rightarrow a+(a+b)+(a+2 b)=-(-6)$
$\Rightarrow 3 a+3 b=6$
$\Rightarrow a+b=2$
$\Rightarrow a=2-b$ ........(i)
Product of all the zeroes $=-($ constant term $)\div$ coefficient of $x^3$
$a(a+b)(a+2 b) =-10$
$(2-b)(2)(2+b) =-10$ [Using equation (i)]
$(2-b)(2+b) =-5$
$4-b^2 =-5$
$\Rightarrow \quad b^2 =9$
$\Rightarrow \quad b = \pm 3$
When $b=3, a=2-3=-1$ [Using equation (i)]
$\Rightarrow a=-1 \text { when } b=3$
$\text { When } b=-3, a=2-(-3)=5$
[Using equation (i)]
$\Rightarrow \quad a=5 \text { when } b=-3 .$
Case 1: when $a=-1$ and $b=3$
The zeroes of the polynomial are :
$a =-1$
$a+b =-1+3=2$
$a+2 b =-1+2(3)=5$
$\Rightarrow-1,2$ and 5 are the zeroes.
Case 2: when $a=5$ and $b=-3$
The zeroes of the polynomial are :
$a =5$
$a+b=5-3=2 $
$a+2 b =5-2(3)=-1$
$\Rightarrow-1,2$ and $5$ are the zeroes.
In both the cases, the zeroes of the polynomial are $-1,2,5$.